Investigating the hydrological significance of stalagmite geochemistry (Mg, Sr) using Sr isotope and particulate element records across the Late Glacial-to-Holocene transition. (15th February 2017) - Belli, R.; Borsato, A.; Frisia, S.; Drysdale, R.; Maas, R.; Greig, A.
Abstract: The trace element and Sr isotope records in two coeval stalagmites characterized by different growth rates and flow regimes at Savi cave (Grotta Savi, NE Italy) reveal different sources and incorporation mechanisms for Mg and Sr. Mg is sourced primarily from dissolved cave host rock while particulate Mg derived from soil plays a subordinate role. The presence of particulate-borne Mg is inferred from the co-variation of Mg and particle-associated elements (Th, Al and Mn) which are preferentially concentrated in open columnar calcite layers. Variation in Mg concentrations corrected for particle-influenced components, the Mgc parameter, is controlled by water–rock interaction, with higher and lower Mgc during dry and wet phases, respectively. This is thought to reflect incongruent dissolution of Mg-rich phases. Correction of Sr concentrations for contributions from airborne exogenic Sr, based on 87 Sr/ 86 Sr ratios, yields the bedrock-only contribution (Src ). Src variation in stalagmite calcite is influenced by speleothem growth rate and by variation of the calcite-water Sr partitioning in wet and dry phases, and only to a minor extent by incongruent dissolution of Mg-rich phases. Concentration profiles for Mgc and Srcg (corrected for growth rate effects) show inverse correlations and are inferred to show hydrological significance which is captured in a hydrological index, HI. We suggest HI provides robust information on water–rock interaction related to hydrological changes and can be utilized in both wet and semi-arid environments, provided the corrections for soil Mg and exogenic Sr can be applied with confidence. Application of the HI index allows correction of Grotta Savi oxygen isotope data, to yield a δ 18 Oc time series that shows when changes in moisture sources and atmospheric reorganization, or changes in moisture amount, were significant. This is especially evident during the Younger Dryas (YD). The Savi record supports the concept of a two-phase YD, marked by an increase of moisture and stronger impact of Adriatic and Mediterranean Sea influences over the northern Adriatic region from 12.3 ka onwards. Then, a large-scale atmospheric reorganization and gradual northward shift of the Polar Front caused a progressive reduction of sea influence over the region from 12.1 ka, supporting the concept of a hemispheric change.